Micro-Apartments: Achieving Spatial Comfort in Substandard Housing Conditions - Alfirević, Đorđe; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2022)
Micro-housing means living in substandard conditions, in housing units that are very small in size. Such apartments usually have only the most basic contents, such as rooms for rest, kitchens and bathrooms, and they do not meet all functionality aspects, because users consciously choose to forego certain living needs in order to live in a certain location or have lower maintenance costs. The research considers characteristic examples of micro-apartments and analyses reference literature, in order to extract design principles from extensive material, through which it is possible to achieve spatial comfort in apartments of minimal dimensions. The aim of the research is to consider and systematize the most important principles that can achieve a higher level of spatial comfort in substandard conditions for micro-housing. The paper examines the view that the lower limit of the range of microhousing is the personal experience of comfort and convenience in the living space, determined by how well it meets the users’ physiological needs. According to the results of the research, in order to have minimum spatial comfort in an apartment, it is necessary to have a rest area (bed), with the possibility of using a common space for food preparation and personal hygiene, which lowers the default lower limit of interpreting the term “micro-housing”